Assessment of incidence of cerebral vascular diseases and prediction of stroke risk in chronic obstructive pulmonary disease patients using multimodal biomarkers - Marwa Y. Badr; Amira A. Elkholy; Sara M. Shoeib; Marwa G. Bahey; Esraa A. Mohamed; Alaa M. Reda (The Clinical Respiratory Journal, 2023)
Abstract Background Early assessment of cerebrovascular disease in chronic obstructive pulmonary disease (COPD) patients is an important issue for a favorable influence on the quality of life. Methodology This cross‐sectional case–control study was conducted on 38 eligible COPD patients (mean age 55.5 ± 11.5, 25 males, and 13 females) and 26 age‐/sex‐matched healthy controls. All participants were subjected to stroke risk screening instruments that included the Stroke Riskometer™, the Framingham 10‐Year Risk Score, the stroke risk screening tool (the Department of Disease Control of Thailand), the My Risk Stroke Calculator, and Q Stroke. Radiologically, diffusion tensor imaging (DTI) and echo‐gradient MRI (T2 star) T2 star imaging were done. Color‐coded duplex sonography was done. Laboratory investigations included C‐reactive protein (CRP), serum amyloid A, plasma fibrinogen level, serum IL6, 8‐Isoprostane, vWF and urinary albumin creatinine ratio. Results Stroke risk screening instruments revealed a significant increase in COPD patients. DTI showed a significant bilateral reduction in fractional isotropy and a significant bilateral increase in mean diffusivity of white matter through many areas in COPD patients. Patients also had a significant increase of intima–media thickness, presence of atherosclerotic focal thicknesses or plaques on duplex sonography. There was a significant elevation of CRP, serum amyloid A, plasma fibrinogen level, serum IL6, 8‐isoprostane, von Willebrand factor (vWF), and urinary albumin creatinine ratio in COPD patients. Conclusion COPD patients had an increased risk for stroke that could be assessed on stroke risk screening instruments, DTI, T2 star, duplex sonography, and laboratory investigation and could be correlated with the severity of the disease.